Causal networks of adverse childhood experience and orthorexia nervosa - Кучина, Валерія (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Introduction. The problem of orthorexia nervosa is becoming increasingly popular not only in Western society, but also in other countries around the world: India, Turkey, China, and many others. The psychological phenomenon and construct of orthorexia nervosa is still seeking its place among other eating disorders and beyond. Diagnostic criteria for nervous orthorexia are still being developed, and attempts are being made to create psychometric tools for it. The purpose of this article is to study the psychogenic component of nervous orthorexia from the perspective of negative childhood experiences (physical and emotional abuse) through the mediating prism of the influence of types of eating behavior (restrictive, emotion-driven, or external) and dysfunctional patterns. To this end, the method of causal modeling with the construction of path diagrams of regression influences was used. As a result, the mechanisms of orthorexic eating behavior were demonstrated for groups of representatives of orthorexic modalities (diagnosed with nervous orthorexia) and control groups (among which were representatives of those who practice fasting of any religious tradition, follow a therapeutic diet due to illness, use weight loss drugs, or do not follow any dietary restrictions at all. This revealed that the development of orthorexia nervosa is largely determined by negative childhood experiences, which particularly influence the orthorexic modalities of exclusion and emphasis. Restrictive, emotion-driven, and external eating behaviors are associated with negative childhood experiences. Schema-regimes are powerful mediators that can either strengthen or weaken orthorexic tendencies. However, control groups have shown that orthorexic manifestations remain within normal limits if there is no traumatic childhood experience.